Do Regulatory Bioequivalence Requirements Adequately Reflect the Therapeutic Equivalence of Modified-Release Drug Products? - Laszlo Endrenyi; Laszlo Tothfalusi (Frontiers Media S.A., 2010)
Purpose. To demonstrate that current regulatory requirements for bioequivalence (BE) do not always reflect therapeutic equivalence. To investigate the potential usefulness of an additional metric, the partial AUC. Methods. Pharmacokinetic information was reviewed and evaluated on the pharmacokinetics of modified-release methylphenidate and nifedipine products. Results. In studies of modified-release products of methylphenidate as well as of nifedipine, traditional regulatory criteria found two formulations to be bioequivalent even though their concentration profiles strongly diverged during the period of absorption. An additional metric, partial AUC, discriminated strongly between the concentrations of the drug products. Conclusions. The current regulatory criteria for the acceptance of BE do not always reflect the therapeutic equivalence of modified-release drug products. With some modified-release products, the application of an additional metric, the partial AUC, yields an improved discriminatory representation.